PENGENALAN LITERASI BUDAYA INDONESIA BERSAMA MAHASISWA REPUBLIK CEKO DI SD 1 SWASTA HKBP SIDORAME - Renita Br Saragih; Vina Merina Br Sianipar; Eka Putri Saptari Wulan; Pontas Jamaluddin Sitorus; Sarah Evelyn Samosir; Nurhayati Theresia Sagala; David Guth; Dusan Jina; Martin Maděra; Matous Havrlik; Jam Tamasov; Lenka Křivánková; David Mrazek (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The implementation of the Cooperation Program with the Indonesian Language and Literature Education Study Program in community dedication with the Republic of Ceko’s students aims to improve cultural and educational literacy at SD 1 Private HKBP Sidorame Medan. The introduction of literacy will provide an accompaniment from teachers and resources so that the students recognize both visual and technological literacy. This is because the level of student literacy is very low so this community dedication activity will develop a social level of cultural diversity and student literacy. This collaboration program was held on July 25, 2022, and ended on July 26, 2022, carried out by lecturers and students from the Faculty of Teacher Training and Education, Indonesian Language and Literature Education Study Program, University of HKBP Nommensen Medan together with students in university Republic of Ceko. Based on the results of the activity, there were positive results with increasing interest in learning about literacy, especially in cultural literacy so that it had an impact on students and teachers. Therefore, teaching creativity is needed for the delivery of literacy and it will become a culture in literacy